Other patients are really in need of medical attention: the quality of health services for rape survivors in South Africa - Nicola J. Christofides; Rachel K. Jewkes; Naomi Webster; Loveday Penn-Kekana; Naeema Abrahams; Lorna J. Martin (The World Health Organization, 2005)
OBJECTIVE: To investigate in the South African public health sector where the best services for rape survivors were provided, who provided them, what the providers' attitudes were towards women who had been raped and whether there were problems in delivering care for rape survivors. METHODS: A cross-sectional study of facilities was carried out. Two district hospitals, a regional hospital and a tertiary hospital (where available) were randomly sampled in each of the nine provinces in South Africa. At each hospital, senior staff identified two doctors and two nurses who regularly provided care for women who had been raped. These doctors and nurses were interviewed using a questionnaire with both open-ended and closed questions. We interviewed 124 providers in 31 hospitals. A checklist that indicated what facilities were available for rape survivors was also completed for each hospital. FINDINGS: A total of 32.6% of health workers in hospitals did not consider rape to be a serious medical condition. The mean number of rape survivors seen in the previous six months at each hospital was 27.9 (range = 9.3-46.5). A total of 30.3% of providers had received training in caring for rape survivors. More than three-quarters of regional hospitals (76.9%) had a private exam room designated for use in caring for rape survivors. Multiple regression analysis of practitioner factors associated with better quality of clinical care found these to be a practitioner being older than 40 years (parameter estimate = 2.4; 95% confidence interval (CI) = 0.7-5), having cared for a higher number of rape survivors before (parameter estimate = 0.02; 95% CI = 0.001-0.03), working in a facility that had a clinical management protocol for caring for rape survivors (parameter estimate = 2; 95% CI = 0.12-3.94), having worked for less time in the facility (parameter estimate = -0.2; 95% CI = -0.3 to -0.04) and perceiving rape to be a serious medical problem (parameter estimate = 2.8; 95% CI = 1.9-3.8). CONCLUSION: There are many weaknesses in services for rape survivors in South Africa. Our findings suggest that care can be improved by disseminating clinical management guidelines and ensuring that care is provided by motivated providers who are designated to care for survivors.